Răspuns :
a)
(+9)-(+11)=
(+9)-11=-2
b)
(-13)-(-4)=
(-13)+4=-9
c)
+43-(-12)=
+43+12=+55
d)
-21-(+19)=
-21-19=-40
e)
4+(-9+5)=
4+(-4)
4-4=0
f)
-11-(+5-4)=
-11-(+1)
-11-1=-12
Sper ca te-am ajutat!
(+9)-(+11)=
(+9)-11=-2
b)
(-13)-(-4)=
(-13)+4=-9
c)
+43-(-12)=
+43+12=+55
d)
-21-(+19)=
-21-19=-40
e)
4+(-9+5)=
4+(-4)
4-4=0
f)
-11-(+5-4)=
-11-(+1)
-11-1=-12
Sper ca te-am ajutat!
1. (+9)-(11)= +9-11
= -2
2. (-13)-(-4)=-13+4
= -9
3. +43-(-12)= +43+12
= +55
4. -21-(+19)= -21-19
= -40
5. 4+(-9+5)=4+( -4)
= 4- 4
= 0
6. -11-(+5-4)= -11-(+1)
= -11-1
= -12
= -2
2. (-13)-(-4)=-13+4
= -9
3. +43-(-12)= +43+12
= +55
4. -21-(+19)= -21-19
= -40
5. 4+(-9+5)=4+( -4)
= 4- 4
= 0
6. -11-(+5-4)= -11-(+1)
= -11-1
= -12